The Right to Health and the Nature of The Right to Health and the Nature of Socio-Economic Rights Obligations under the African Charter - Mbazira, Christopher (Economic and Social Rights in South Africa, 2005)
The African Charter on Human and Peoples’ Rights (the African Charter) guarantees a broad range of economic, social and cultural rights (socio-economic rights) as well as civil and political rights.